The crystal structure of N,N′-(1,2-phenylene)bis (2-((2-oxopropyl)selanyl)benzamide), C26H24N2O4Se2 - Feng Shuxiao; Zhong Xuan; Qi Kaiyan; Guo Yafei; Wang Junling; Gu Guangna; Ma Junying (Zeitschrift für Kristallographie - New Crystal Structures)
C26H24N2O4Se2, monoclinic, C2/c (no. 15), a = 22.9092(7) Å, b = 5.8900(2) Å, c = 36.6209(9) Å, β = 91.983(3)°, V = 4938.5(3) Å3, Z = 8, R gt(F) = 0.0419, wR ref(F 2) = 0.1162, T = 293 K.